2021
DOI: 10.1016/j.jiph.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors for death in patients with coronavirus disease-2019 (COVID-19) pneumonia admitted to the intensive care units of an Egyptian University Hospital. A retrospective cohort study

Abstract: Background The characteristics, outcomes, and risk factors for in-hospital death of critically ill intensive care unit (ICU) patients with coronavirus disease-2019 (COVID-19) have been described in patients from Europe, North America and China, but there are few data from COVID-19 patients in Middle Eastern countries. The aim of this study was to investigate the characteristics, outcomes, and risk factors for in-hospital death of critically ill patients with COVID-19 pneumonia admitted to the ICUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“…Nassar et al studied the characteristics, outcomes, and risk factors for inhospital death of critically ill patients with COVID-19 pneumonia admitted to Cairo University Hospitals in Egypt, where chronic liver disease patients had the lowest incidence of all comorbidities, with zero mortality [ 36 ]. A retrospective study identifying risk factors of patients requiring ICU admission during hospital stay was collected from Ain Shams University Isolation-Hospital which records low incidence of ward admission with Zero ICU admission [ 37 ].…”
Section: Evidence Synthesis For the Hypothesismentioning
confidence: 99%
“…In the Middle East, four studies evaluated predictors of COVID-19 severity and mortality [ 17 , 18 , 19 , 20 ]. One of these studies, conducted in Kuwait, showed that patients with heart disease, kidney disease, abnormal inflammatory markers, and abnormal coagulation had higher COVID-19 severity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%